SMALL CANTATAS IN THE CZECH COMPOSITIONS FOR CHILDREN extasciiacuteS CHOIR IN THE 20th CENTURY - Buresova, Alena (Musicologica Olomucensia, 2001)
The modern progress of children extasciiacutes choirs in the 20th century has demonstrated the ability of children to present the most highly artistically demanding compositions. The Czech choral literature is represented by more than 300 authors of this genre, about 80 of whom are considered to be prestigious.The cantata has a special place in the rich repertoire. Small cantatas with chamber orchestra or a capella (without accompaniment by musical instruments) are representative for interpretation by children extasciiacutes choirs. These cantatas are highly challenging both in terms of content and technical demands and therefore serve as good examples od the maximum that children have been thus far capable od achieving. Common humanitarian thoughts are found especially in the a capella cantatas (for example: Petr Reznicek, Evzen Zamecnik), the contents of which are comprehensible to children both mentally and psychologically, while nevertheless satisfying also the adult public through their poetics.The centric hierarchy of the musical shape from diatonic to broadened tonality, modality and modern chordality dominates in the majority od these compositions. Polyphony is amalgamated with folkloric themes and also with the new compositional techniques of the 20th century: athematic style, dodecaphony, rule-aleatoric, assembly, stratophony, etc. At the same time, a characteristic tendency to synthetize both traditional and modern progressive styles is also manifested here. The combination of the timbre and aleatoric, exact construction with a multi-dimensional span of harmonic, rhythmic and melodic textural layers are observable in these compositions (for example: Ctirad Kohoutek, Ivo Jirasek, Miroslav Raichl).